The effect of smoke derivatives and carbon utilisation on symbiotic germination of the endangered Pterostylis despectans - Ritmejeryté, Edita; Obvintseva, Anna; Huynh, Tien (Lankesteriana: International Journal on Orchidology, 2018)
Orchids are highly dependent on exogenous nutritional sources and mycorrhizal associations to survive, particularly when challenged by extreme environmental stress such as bushfires that contribute significantly to its existence in nature. In this study, the effect of smoke derivatives and carbon utilisation was explored to improve germination and seedling establishment of an Australian endangered orchid, Pterostylis despectans (Lowly Greenhood) and on mycorrhizal fungi to improve its survivorship in the rhizosphere and functionality on host plants. Stored seeds were germinated in vitro with peloton-isolated fungal isolates with varying concentrations of smoke water (0–1.0 mL L-1) to simulate fire and sucrose as the carbon source (10 g L-1). Smoke water significantly increased germination, with advanced protocorms and robust seedlings produced. Sucrose inhibited germination such that protocorms and leafing was absent with sucrose inclusion. Fungal isolates were highly variable on its germination efficacy and tolerance to smoke water, highlighting the importance of fungal diversity and supports research-based conservation strategies to circumvent environmental challenges.